![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(2x^2-4xy+2y^2-8z^2=2\left(x^2-2xy+y^2-4z^2\right)=2\left[\left(x-y\right)^2-\left(2z\right)^2\right]\)
\(=2\left(x-y-2z\right)\left(x-y+2z\right)\)
b) \(x^3-3x^2-4x+12=x^2\left(x-3\right)-4\left(x-3\right)=\left(x^2-4\right)\left(x-3\right)=\left(x-2\right)\left(x+2\right)\left(x-3\right)\)
![](https://rs.olm.vn/images/avt/0.png?1311)
e) Ta có: \(a^3-a^2-a+1\)
\(=a^2\left(a-1\right)-\left(a-1\right)\)
\(=\left(a-1\right)\left(a^2-1\right)\)
\(=\left(a-1\right)^2\cdot\left(a+1\right)\)
f) Ta có: \(x^3-2xy-x^2y+2y^2\)
\(=x^2\left(x-y\right)-2y\left(x-y\right)\)
\(=\left(x-y\right)\left(x^2-2y\right)\)
a) \(\left(a^2+b^2\right)^2-4a^2b^2=\left(a^2+b^2+2ab\right)\left(a^2+b^2-2ab\right)=\left(a+b\right)^2.\left(a-b\right)^2\)
b) \(3x^2-3xy-5x+5y=3x\left(x-y\right)-5\left(x-y\right)=\left(x-y\right)\left(3x-5\right)\)
c) \(-x^3+3x^2-3x+1=\left(1-x\right)^3\)
d) Đề sai ko ???
e) \(a^3-a^2-a+1=a^2\left(a-1\right)-\left(a-1\right)=\left(a-1\right)\left(a^2-1\right)=\left(a-1\right)^2\left(a+1\right)\)
f) \(x^3-2xy-x^2y+2y^2=x^2\left(x-y\right)-2y\left(x-y\right)=\left(x-y\right)\left(x^2-2y\right)\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(x^2-x-xy-2y^2+2y\)
\(=x^2-x-2xy+xy-2y^2+2y\)
\(=\left(-2y^2-2xy+2y\right)+\left(xy+x^2-x\right)\)
\(=2y\left(-y-x+1\right)+x\left(y+x-1\right)\)
\(=-2y\left(y+x-1\right)+x\left(y+x-1\right)\)
\(=\left(x-2y\right)\left(y+x-1\right)\)
b) \(x^2+4xy+2x+3y^2+6y\)
\(=x^2+3xy+xy+2x+3y^2+6y\)
\(=\left(3y^2+3xy+6y\right)+\left(xy+x^2+2x\right)\)
\(=3y\left(y+x+2\right)+x\left(y+x+2\right)\)
\(=\left(3y+x\right)\left(y+x+2\right)\)
![](https://rs.olm.vn/images/avt/0.png?1311)
Bài 3:
a: =>(2x-7)(x-2)=0
=>x=7/2 hoặc x=2
b: =>(x-1)(x+2)=0
=>x=1 hoặc x=-2
d: =>2x+3=0
hay x=-3/2
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(x-xy+y-y^2=x\left(1-y\right)+y\left(1-y\right)=\left(x+y\right)\left(1-y\right)\)
b) \(x^2-2x-y^2+1=\left(x^2-2x+1\right)-y^2=\left(x-1\right)^2-y^2=\left(x-y-1\right)\left(x+y-1\right)\)
c) \(4x^2-4xy+y^2=\left(2x\right)^2-2.2x.y+y^2=\left(2x-y\right)^2\)
d) \(9x^3-9x^2y-4x+4y=9x^2\left(x-y\right)-4\left(x-y\right)=\left(9x^2-4\right)\left(x-y\right)=\left(3x-2\right)\left(3x+2\right)\left(x-y\right)\)
e) \(x^3+2+3\left(x^3-2\right)=x^3+2+3x^3-6=4x^3-4=4\left(x^3-1\right)=4\left(x-1\right)\left(x^2+x+1\right)\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(x^3+2x^2+x=x\left(x^2+2x+1\right)=x\left(x+1\right)^2\)
\(5x^2+10x-5y^2+5==5\left(x^2+2x+1-y^2\right)=5\left[\left(x+1\right)^2-y^2\right]=5\left(x+1-y\right)\left(x+1+y\right)\)
\(4x^3-8x^2y+4xy^2=4x\left(x^2-2xy+y^2\right)=4x\left(x-y\right)^2\)
\(x^3+9x^2y-xy=x\left(x^2+9xy-y\right)\)
a) \(x^3+2x^2+x=x\left(x^2+2x+1\right)=x\left(x+1\right)^2\)
b) \(-5x^2+10x-5y+5=-5\left(x^2-2x+y-1\right)\)
c)\(4x^3-8x^2y+4xy^2=4x\left(x^2-2xy+y^2\right)=4x\left(x-y\right)^2\)
d) \(x^3+9x^2y-xy=x\left(x^2+9xy-y\right)\)
![](https://rs.olm.vn/images/avt/0.png?1311)
1b.=2((x+y)+(x+y)(x-y)+(x-y))=2(x2-y2+x+y+x-y)=2(x2-y2+2x)=2x2-2y2+4x
2a.=4xy+4xy+2y=8xy+2y=2y(4x+1)
b.=(3x)2+2.3x.y+y2-(2z)2=(3x+y)2-(2z)2=(3x+y-2z)(3x+y+2z)
c.=x2-x-7x+7=x(x-1)-7(x-1)=(x-1)(x-7)
\(\left(x+y\right)^2+2\left(x+y\right)\left(x-y\right)+\left(x-y\right)^2\)
\(=\left(x+y+x-y\right)^2\)
\(=\left(2x\right)^2\)
\(=4x^2\)
hk tốt
^^
![](https://rs.olm.vn/images/avt/0.png?1311)
a) Xem lại đề
b) x³ - 4x²y + 4xy² - 9x
= x(x² - 4xy + 4y² - 9)
= x[(x² - 4xy + 4y² - 3²]
= x[(x - 2y)² - 3²]
= x(x - 2y - 3)(x - 2y + 3)
c) x³ - y³ + x - y
= (x³ - y³) + (x - y)
= (x - y)(x² + xy + y²) + (x - y)
= (x - y)(x² + xy + y² + 1)
d) 4x² - 4xy + 2x - y + y²
= (4x² - 4xy + y²) + (2x - y)
= (2x - y)² + (2x - y)
= (2x - y)(2x - y + 1)
e) 9x² - 3x + 2y - 4y²
= (9x² - 4y²) - (3x - 2y)
= (3x - 2y)(3x + 2y) - (3x - 2y)
= (3x - 2y)(3x + 2y - 1)
f) 3x² - 6xy + 3y² - 5x + 5y
= (3x² - 6xy + 3y²) - (5x - 5y)
= 3(x² - 2xy + y²) - 5(x - y)
= 3(x - y)² - 5(x - y)
= (x - y)[(3(x - y) - 5]
= (x - y)(3x - 3y - 5)
2x2 + 4xy + 2y2 - 8z2
= 2( x2 + 2xy + y2 - 4z2 )
= 2[ ( x2 + 2xy + y2 ) - 4z2 ]
= 2[ ( x + y )2 - ( 2z )2 ]
= 2( x + y - 2z )( x + y + 2z )
a3 - a2 - a + 1
= ( a3 - a2 ) - ( a - 1 )
= a2( a - 1 ) - ( a - 1 )
= ( a - 1 )( a2 - 1 )
= ( a - 1 )( a - 1 )( a + 1 )
= ( a - 1 )2( a + 1 )
a) 2x2 + 4xy + 2y2 - 8z2
= 2(x2 + 2xy + y2) - 2.4z2
= 2.(x + y)2 - 2.(2z)2
= 2[(x + y)2 - (2z)2]
= 2(x + y + 2z)(x + y - 2z)
b) a3 - a2 - a + 1
= a2(a - 1) - (a - 1)
= (a2 - 1)(a - 1)
= (a - 1)(a + 1)(a - 1)
= (a - 1)2.(a + 1)